HBR's 10 must reads 2016 : (Massachusetts Harvard Business Review Press, 2016)
We’ve examined the ideas, insights, and best practices from the past year of Harvard Business Review to bring you the latest, most significant thinking driving business today. With authors from Marcus Buckingham to Herminia Ibarra and company examples from Google to Deloitte, this volume brings the most current and important management conversations to your fingertips.